Chophouse Row: Merging Past, Present & Future - SKL Architects; Graham Baba Architects (urbanNext, 2018)
Chophouse Row is conceived as a way to merge past, present and future, repurposing existing structures and knitting new and old together in a forward-looking prototype that stimulates and supports its neighborhood. Created from a collection of contiguous properties within a single block in Seattle$1 (Bs Capitol Hill neighborhood, the design puts in place the last phase of a larger vision and master plan developed by the client. Rather than consider the eclectic mix of buildings and empty space an impediment to development, the owner recognized the value of the structures$1 (Bhard-won patina and unique character. By integrating a diverse, mutually supportive combination of activities that includes living, working, and retail in one contiguous array of spaces, the development results in a village within a village.s
FULL, Graham Baba Architects, Middle Density, Project, SKL Architects, Territory and mobility, Urban Paradigms
Active Public Spaces, Agency of Urban Organization, City views, Connections, Courtyard, Future Urban Legacy Lab, Housing, Mixed uses, Mixed-use buildings, Open systems, Project, Refurbishment, Retail, Seattle, Second life, Territorial Approach, Urban Legacy, Urban Paradigms, USA, Washington, Wood
Keywords: Architecture; Multi-use Space; Prototype; Seattle, Washington, USA; USA